Drafting during swimming improves efficiency during subsequent cycling - Delextrat, A.; Tricot, V.; Bernard, T.; Vercruyssen, F.; Hausswirth, C.; Brisswalter, J. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The aim of the present study was to investigate the effects of drafting (i.e., swimming directly behind a competitor) while swimming with a wet suit on physiological parameters and cadence during subsequent cycling. METHODS: Eight well-trained male triathletes underwent two submaximal sessions conducted in a counterbalanced order. One of these sessions (SAC) consisted of a 750-m swim, performed at competition pace, followed by a 15-min ride on a bicycle ergometer at 75% of maximal aerobic power and at a freely chosen cadence. During the other session (SDC) the subjects swam 750 m in a drafting position at the same pace as during SAC and then performed the 15-min cycling test at the same intensity as during SAC. RESULTS: The main result indicated that cycling efficiency was significantly improved when the cycling session was preceded by a swimming bout performed in drafting position compared with an isolated swimming bout (+4.8%, P < 0.05). CONCLUSION: These results could be partly explained by the lower relative intensity observed during swimming in the SDC trial when compared with the SAC trial. This study suggests the relative importance of swimming condition and highlights the advantage of drafting during the swimming portion of a sprint triathlon.